Poética e antipoética do genocídio negro brasileiro: um estudo da literatura dramática de Abdias Nascimento, em Sortilégio II - Silva, Karina de Morais e (2022)
Our research is based on the concepts of poetics and antipoetics of genocide developed by Antônio Paulo Graça (1998), which are configured as theoretical-critical operators relevant to the understanding of a genocidal imaginary that is aesthetically projected in literary works, mobilizing them for understanding of the representative and narrative treatment traditionally given to black people in Brazilian literature. Our thesis is that national literary productions are formed crossed by the action of an anti-black genocidal imagery; element that integrates the narrative structure of the works, despite the motivations of their authors. The performance of this imaginary is demonstrated by its materialization as a poetics in works that are part of the canon or other instances of legitimization of our literature. In this context, we contrast this genocidal poetics to the production of a counter-aesthetics elaborated - at different times and through different forms - by the black-Brazilian community. In this sense, we study the productions of Teatro Experimental do Negro, founded by Abdias Nascimento, as a projection and composition of an antigenocidal aesthetic, and, emphasizing its dialectical relationship with the national tradition previously considered, as anti-poetic to genocide. The Teatro Experimental do Negro is founded as a political and artistic reaction to the ongoing black genocide, attests Nascimento (2016). Based on this, we analyze his play Sortilégio II: mistério negro redivivo, in order to demonstrate how the author's dramatic literature, located in the artistic-cultural movement of which he is a part, demarcates aesthetic motives, strategies and procedures that make up the antipoetics of black genocide . The fundamental studies by Abdias Nascimento (2016; 2019) for the understanding of the genocide of the Brazilian black people and the manifestation of this genocide in the sphere of culture participate in the theoretical foundation of our research; the notions and concepts operated by Antônio Paulo Graça to define and interpret a poetics of genocide (1998); the tradition of historical and sociological studies that, as a whole, allow us to trace the history and understand the structuring of black genocide in Brazil, including Florestan Fernandes (2007; 2017), Clóvis Moura (2019), Lélia González (2020); João Costa Vargas (2010); studies on the representation of the black person in Brazilian literature, such as those by Roger Bastide (1983), David Brookshaw (1983) and Heloisa Toller Gomes (1988) and Leda Maria Martins (1995); the literature of writers Solano Trindade, Carlos Assumpção, Conceição Evaristo and Dinha, mobilized as conceptual and testimonial potentialities of the anti-black genocide.